1968
DOI: 10.1246/bcsj.41.342
|View full text |Cite
|
Sign up to set email alerts
|

Ca3(PO4)2 - CaNaPO4 System

Abstract: As a fundamental research of a calcined defluorinated phosphate containing a small amount of sodium, the system Ca3(PO4)2(tricalcium phosphate, T) - CaNaPO4(Rhenanite, R) was studied by high temperature X-ray diffraction, differential thermal analysis, etc., and the phase diagram determined. During heating, T inverted from β to α at 1180°C, and then possibly from α to α′ at 1280°C. R inverted from β to α at 690°C. In the composition range containing R from about 10 to 98% by weight, (βT+βR), the stable phase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Ando and Matsuno [19] have investigated the Ca 3 (PO 4 ) 2 -CaNaPO 4 system and confirmed that the structure of Ca 20 Na 2x (P 2 O 7 ) 1Àx (PO 4 ) 12+2x can be formed. These products are stable under the condition of preparation in the range 0pxp1, which is equivalent to the synthesized product from DCPD in this study.…”
Section: Crystal Structure Of Ha Powders With Various Ca/p Ratiomentioning
confidence: 82%
See 1 more Smart Citation
“…Ando and Matsuno [19] have investigated the Ca 3 (PO 4 ) 2 -CaNaPO 4 system and confirmed that the structure of Ca 20 Na 2x (P 2 O 7 ) 1Àx (PO 4 ) 12+2x can be formed. These products are stable under the condition of preparation in the range 0pxp1, which is equivalent to the synthesized product from DCPD in this study.…”
Section: Crystal Structure Of Ha Powders With Various Ca/p Ratiomentioning
confidence: 82%
“…(2) is supposed to have a slow reaction rate which starts at 650 C and continues even above 1000 C. In this study, b-TCP is not found in the sample after annealing above 600 C, which means that b-TCP is excluded by some other reactions. Ando and Matsuno [19] have investigated the Ca 3 (PO 4 ) 2 -CaNaPO 4 system and claimed that at high temperatures CaNaPO 4 dissolves large amounts of Ca 3 (PO 4 ) 2 . In the Ca 3 (PO 4 ) 2 -CaNa-PO 4 system, b-TCP disappears during heating between 650 C and 980 C, containing CaNaPO 4 from 50.5% to 97% to form an a-rhenanite solid solution.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffraction confirmed that this complex phosphate is isostructural with Ca^a-tPO. ), -phase 'A' described by Ando and Matsuno (1968). These authors note that phase 'A' is soluble in weak citric acid solutions.…”
Section: Experimental Studies (A) Strategymentioning
confidence: 99%
“…The phase equilibria defined by Ando and Matsuno (1968) reveal that at 1200-1300°C, there is substantial mutual solid solution between…”
Section: T _mentioning
confidence: 99%
“…This study was limited to that of mixtures in a temperature range determined by previous results. The pcesent work confirms the existence of two metastable diagrams which are superimposed on the stable diagram.The experimental conditions leading to the formation of the metastable phases on cooling (cooling rate and highest temperature reached before cooling) and to the different types of metastability were determined from the differential X-ray diffraction spectra.L'dtablissement du diagramme de phase des dquilibres solide-solide du syst~me Ca3(PO4)2-CaNaPO4 par analyses thermiques directe et diffdrentielle coupldes a fait I'objet d'une premiere sdrie d'~tudes [1][2][3].Diff~rents diagrammes de phase avaient auparavant dtd proposals pour ce syst~me [4,5]. Ces diffdrences, portant sur les limites du domaine d'existence d'une phase non stoechiom6trique (phase A) stable ~ haute temp6rature, ont pu ~tre expliqu6es par la mise en 6vidence de deux diagrammes mdtastables pouvant ~tre d~crits au refroidissement.…”
mentioning
confidence: 99%